Aggregates segregation in rubberized mortar. (August 2020) - Moreno, Diego David Pinzón; Ribeiro, Sebastião; Saron, Clodoaldo
Abstract: The aggregates segregation in mortars is an event that lead to the formation of a properties gradient along size of the piece, affecting the mechanical performance of the material. In rubberized mortars, the rubber particles are less dense than other aggregates and it can causes considerable segregation effect, depending on the material processing conditions. In present study, the rubber segregation in mortar has been evaluated by image analysis in specimens prepared with various mechanical vibration and water content. For it, specimens of rubberized mortar were prepared on controlled conditions as well as axially cut and polished. A method was created, defining the sample surface in levels, in order to evaluate the rubber segregation. The result obtained showed that rubber segregation is strongly affected by the water content used in the mortar preparation, while the effects related to the vibration time are less significant. The increasing rubber content in the mortar lead also to a gradual decrease in compressive strength and apparent density of the material. The present study allowed establishing limit parameters for the processing of rubberized mortar in order to avoid considerable rubber segregation.